IDIOMATIC EXPRESSIONS AND PHRASE EXPRESSIONS IN ”DIARY OF A WIMPY KID: THE LONG HAUL” FILM BY DAVID BOWERS - Muhamad Khamim (INFERENCE: Journal of English Language Teaching, 2022)
The aim of the research to find and classify types of Idiomatic Expressions and Phrase Expressions in “Diary of a Wimpy Kid: The Long Haul” Film by David Bowers. In this research the researcher used qualitative approach, like analyze descriptive narration, a dialog or conversation. Meanwhile, for technique data research by content analysis research. The researcher used Lim’s theory to classify idiomatic expressions. In Lim’s theory there are 6 types of idioms, such as: idioms with phrasal verb, idioms with prepositional phrase, idioms with verbs as keyword, idioms with nouns as keyword, idioms with adjective as keyword, and idiomatic pairs. The result of this research showed that the film used 60 idiom expressions to express their feeling and thought. The researcher found 21 Phrasal Verbs, 19 Verb as Keywords, 8 Adjective as Keywords, 6 Noun as Keywords, 3 Prepositional Phrases and 3 Idiomatic pairs. The researcher used Ba’dulu’s theory to examine phrase expressions. In Ba’dulu’s theory there are 5 types of phrase, such as: noun phrase, verb phrase, prepositional phrase, adjective phrase, and adverb phrase. The result of this research showed that the film used 157 phrases. The researcher found 56 Noun Phrases, 48 Verb Phrases, 23 Prepositional Phrases, 18 Verb Phrases and 12 Adverb Phrases.